Evaluation of testosterone and prolactin hormones levels in erectile dysfunction patients after single oral dose of Tadalafil - Hayder Hamed Abed (College of Pharmacy / Mustansiriyah University, 2008)
Erectile dysfunction (ED) is defined as a consistent inability to sustain an erection sufficient for sexual intercourse. Tadalafil is a selective, reversible inhibitor of cyclic guanosine monophosphate (cGMP)-specific phosphodiesterase type 5 (PDE5). When sexual stimulation causes the local release of nitric oxide, inhibition of PDE5 by tadalafil produces increased levels of cGMP in the corpus cavernosum. This results in smooth muscle relaxation and inflow of blood into the penile tissues, thereby producing an erection. Tadalafil has no effect in the absence of sexual stimulation. Erection dysfunction could attribute abnormal levels of testosterone and prolactin levels. Twenty Iraqi patients with different levels of ED were considered in this study treated with 20 mg. of tadalafil coated tablets. All patients considered in this study have been get erection after treatments with tadalafil. Prolactin and testosterone has been determined by radioimmunoassay (RIA). The evaluated results indicated significant decrease for prolactin (p<0.01) and significant elevation for the testosterone (p<o.ooo1). The ratio of prolactin/ testosterone was increased after treatments. In conclusion: prolactin and testosterone hormonal levels must be considered with tadalafil treatments. Tadalafil must be not described to patients with abnormal levels of these hormones. Patients with testosterone and prolactin abnormalities need to take advice from the endocrinologist before use tadalafil with monitoring of prolactin and testosterone levels.